Gene Expression Analysis of Early Stage Endometrial Cancers Reveals Unique Transcripts Associated with Grade and Histology but Not Depth of Invasion - Risinger, John; Allard, Jay; Chandran, Uma; Day, Roger; Chandramouli, Gadisetti; Miller, Caela; Zahn, Christopher; Oliver, Julie; Litzi, Traci; Marcus, Charlotte; Dubil, Elizabeth; Byrd, Kevin; et al. (Frontiers in Oncology, 2013)
Endometrial cancer is the most common gynecologic malignancy in the United States but it remains poorly understood at the molecular level. This investigation was conducted to specifically assess whether gene expression changes underlie the clinical and pathologic factors traditionally used for determining treatment regimens in women with stage I endometrial cancer. These include the effect of tumor grade, depth of myometrial invasion and histotype. We utilized oligonucleotide microarrays to assess the transcript expression profile in epithelial glandular cells laser microdissected from 79 endometrioid and 12 serous stage I endometrial cancers with a heterogeneous distribution of grade and depth of myometrial invasion, along with 12 normal post-menopausal endometrial samples. Unsupervised multidimensional scaling analyses revealed that serous and endometrioid stage I cancers have similar transcript expression patterns when compared to normal controls where 900 transcripts were identified to be differentially expressed by at least 4-fold (univariate t-test, p <0.001) between the cancers and normal endometrium. This analysis also identified transcript expression differences between serous and endometrioid cancers and tumor grade, but no apparent differences were identified as a function of depth of myometrial invasion. Four genes were validated by quantitative PCR on an independent set of cancer and normal endometrium samples. These findings indicate that unique gene expression profiles are associated with histologic type and grade, but not myometrial invasion among early stage endometrial cancers. These data provide a comprehensive perspective on the molecular alterations associated with stage I endometrial cancer, particularly those subtypes that have the worst prognosis.